Freshwater snails and schistosomiasis mansoni in the state of Rio de Janeiro, Brazil: VI - Noroeste Fluminense Mesoregion - Silvana C Thiengo; Aline C Mattos; Sonia B Santos; Monica A Fernandez (Memorias do Instituto Oswaldo Cruz, 2006)
In this paper, the last of a series dealing with the survey of freshwater gastropods of the state of Rio de Janeiro, the results of collections carried out in the Noroeste Fluminense Mesoregion from 2002 to 2005 are presented and revealed the occurrence of 20 species: Antillorbis nordestensis; Biomphalaria glabrata; B. straminea; B. tenagophila; Drepanotrema anatinum; D. cimex; D. depressissimum; D. lucidum; Ferrissia sp.; Gundlachia ticaga; Gundlachia sp.; Heleobia sp.; Idiopyrgus sp.; Lymnaea columella; Melanoides tuberculatus; Physa acuta; P. marmorata; Plesiophysa guadeloupensis; Pomacea lineata; and Pomacea sp. Concerning the snail hosts of schistosomiasis the three natural vectors were identified and, although no specimens were found harbouring larval forms of Schistosoma mansoni, different kinds of cercariae had been observed.